Organization and management of nursing services in specialized tertiary hospitals in Metro Manila - Malana, Basilisa E.
This study was conducted in order to help the new nursing service administrator to organize and manage a nursing service department; in this study, the nursing service in a tertiary set-up. A case study was conducted in 3 specialized tertiary hospitals in Metro Manila which were selected at random from March, 1985 to January, 1986. 4 research instruments, namely: interview schedule, questionnaire, observation checklist, and documentary analysis were utilized. A checklist of tangible evidences of a well-organized nursing service was also accomplished. A questionnaire-checklist was distributed to 20 of the professional nursing personnel from each hospital. Herberg's 2-Factor Theory was used to reveal the reaction of the nurses to some management functions. Questionnaires were also distributed at randomm to 20 of the patient population to document reactions to the performance of the professional nurse. Findings of the study showed varied results. The 3 specialized tertiary hospitals used different organizational strategies and management corresponding data presented. Each of the founding nursing director presented various qualifications. Each of them merited their good and bad points. This study was formulated as a guide which could serve as a starting point to a beginning nursing director who is tasked to start a nursing service from zero. This does not mean that the nurse practitioner stops from here. The guide has to be expanded and broadened with stock and new knowledge. A person keeps searching for more; a nursing director is never satisfied with 1 accomplishment, she moves on to face the technological advances and development to create provinces for the delivery of an optimum and best nursing care to the target clientile.